The determination of green open space (GOS) in Palu based on total population and area - Astutiek, P; Chaerul, A; Julia, F (ASCEE, 2022)
Green Open Space (GOS) is the most important factor of a city formation structure. Green open space is very much needed around the downtown area due to its function that supports the ecology of a city. The quality of environment are becoming healthier hence the function of green open space as a recreation area in the downtown. Green Open Space can also function as a spot where people are able to socially interact with each other, function in culture aspect and even function as an area to support the economy of the community around the existence of the green open space. Urban area of Palu city has high temperature because it passed by the equator, sometimes it reaches 36 ℃, even if it is raining during the night but still it is very hot in the daylight. Determination of how green open space starts is from population density and area, it can be seen through several sub-districts because the population of each sub-district is different in terms of number and area. Therefore, it should be regulated from several existing districts. Palu City consists of 8 districts with varying population densities. Method used was quantitative analysis through calculating the need for green open space based on thepopulation in each district. The data were analyzed through the formula and the coefficient per capita. Then it is described in maps of sub-districts in the city of Palu. The results of this research will provide how many public open space is spread in the city of Palu as the capital of Central Sulawesi Province. This can be applied to the map of Palu City. The results of the research will show how many public open spaces are in each sub-district.